2015
DOI: 10.3892/mmr.2015.4114
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear transcription factor CDX2 inhibits gastric cancer-cell growth and reverses epithelial-to-mesenchymal transition in vitro and in vivo

Abstract: The epithelial‑to‑mesenchymal transition (EMT) has been noted as a critical event in the early step of cancer metastasis. Recent studies showed that nuclear transcription factor caudal type homeobox transcription factor 2 (CDX2) is a prognostic factor, which acts as a marker of good outcome in gastric cancer (GC) patients. However, the association between CDX2 expression and EMT has remained to be fully elucidated. The present study reported that forced overexpression of CDX2 in MKN45/CDX2 cells inhibited GC‑c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
1
14
3
Order By: Relevance
“…However, another study showed that CDX2 overexpression suppressed cell migration and invasion in MGC-803 cells and that CDX2 silencing promoted migration and invasion in NCI-N87 cells [33], indicating that CDX2 may inhibit migration and invasion of gastric cancer cells. Moreover, another report showed that ectopic expression of CDX2 reduced migration and invasion in MKN-45 cells [36], which is contrary to our ndings in MKN-45 cells. The inconsistency in these results may be due to the different gastric cancer cell lines used in the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…However, another study showed that CDX2 overexpression suppressed cell migration and invasion in MGC-803 cells and that CDX2 silencing promoted migration and invasion in NCI-N87 cells [33], indicating that CDX2 may inhibit migration and invasion of gastric cancer cells. Moreover, another report showed that ectopic expression of CDX2 reduced migration and invasion in MKN-45 cells [36], which is contrary to our ndings in MKN-45 cells. The inconsistency in these results may be due to the different gastric cancer cell lines used in the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…However, it is ectopically expressed in IM lesions of the stomach and intestinal-type gastric carcinoma [1][2][3][4][5][6][7][8]. Several studies have reported that CDX2 acts as a tumor suppressor in gastric cancer [6][7][8][21][22][23][24][25][26][27][28][29][30][31]. However, others consider CDX2 an oncogene in gastric cancer [1,2,[9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that the CDX2 gene promoter was highly methylated in human MKN45 gastric cancer cell line, and the expression levels of CDX2 mRNA were extremely low and CDX2 protein was not expressed. After incubation with three levels of 5-aza-CdR (inhibitor of methylation) for 72 h, the expression levels of CDX2 mRNA and protein were upregulated in MKN45 cells ( 11 ). However, it was reported that the expression of CDX2 gene was related to post-transcriptional regulation, such as the phosphorylation of CDX2 protein, rather than epigenetic modification (DNA methylation, histone acetylation) ( 12 ).…”
Section: Discussionmentioning
confidence: 99%